2019
DOI: 10.3389/fphys.2019.01340
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Cholesterol-Rich Membrane in Oxygen Adaption: The Respiratory System as a Model

Abstract: The increase in atmospheric oxygen levels imposed significant environmental pressure on primitive organisms concerning intracellular oxygen concentration management. Evidence suggests the rise of cholesterol, a key molecule for cellular membrane organization, as a cellular strategy to restrain free oxygen diffusion under the new environmental conditions. During evolution and the increase in organismal complexity, cholesterol played a pivotal role in the establishment of novel and more complex functions associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 201 publications
(251 reference statements)
2
9
0
Order By: Relevance
“…This is also reported for lung tissues, where cholesterol-rich areas of the membrane were suggested to react to control the oxygen diffusion. 53 Our findings in Caco-2 cells also are in line with previous results, 54 which showed that 18 h exposure to hypoxia does not result in alteration in total cholesterol level of primary epithelial monolayer cells.…”
Section: Discussionsupporting
confidence: 92%
“…This is also reported for lung tissues, where cholesterol-rich areas of the membrane were suggested to react to control the oxygen diffusion. 53 Our findings in Caco-2 cells also are in line with previous results, 54 which showed that 18 h exposure to hypoxia does not result in alteration in total cholesterol level of primary epithelial monolayer cells.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, LPS makes the bacterial outer membrane impermeable to hydrophobic compounds ( 58 60 ), and so does LOS in C. jejuni ( 34 ). Oxygen, as a small nonpolar molecule, can freely diffuse across biological membranes ( 61 , 62 ). However, the hydrophilic polar headgroup regions of phospholipids are barriers to oxygen permeation through membranes ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The last step oxygen encounters in its way to the rest of the organs is the erythrocyte membrane. Red blood cells present a rather high cholesterol content, which comprises a 1:1 phospholipid to cholesterol ratio (Zuniga-Hertz and Patel, 2019). In addition, it has been described that oxygen diffusion through red blood cell membranes is decreased in the presence of increased cholesterol content (Buchwald et al, 2000).…”
Section: Why Is Cholesterol Present In the Lung?mentioning
confidence: 99%